2009
DOI: 10.1080/13540600802661311
|View full text |Cite
|
Sign up to set email alerts
|

It’s the little things: exploring the importance of commonplace events for early‐career teachers’ motivation

Abstract: This paper seeks to provide a rationale for further researching the everyday events that keep teachers motivated or that discourage them. We put forward the idea that routine Affect Triggering Incidents (ATIs) are an important area for researchers to investigate in terms of how they impact teacher motivation and resilience. Two groups of participants in separate consecutive studies kept weekly diaries of incidents that made them feel good or bad about themselves in their work as teachers (Study 1) and added we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 40 publications
7
64
0
3
Order By: Relevance
“…Teachers also expressed a sense of confidence and efficacy in relation to the teaching of reading in this way and therefore teacher efficacy was transferred to the personal level as it is connected with teachers' beliefs in their power to effect change, with correlations between affect and efficacy (Kitching et al, 2009). Similarly, some teachers' experience of this literacy practice led to changes in beliefs and values about collaborative practices among teachers, which in turn led to the adoption of other collaborative practices.…”
Section: Into Practice -Degree and Quality Of Changementioning
confidence: 99%
“…Teachers also expressed a sense of confidence and efficacy in relation to the teaching of reading in this way and therefore teacher efficacy was transferred to the personal level as it is connected with teachers' beliefs in their power to effect change, with correlations between affect and efficacy (Kitching et al, 2009). Similarly, some teachers' experience of this literacy practice led to changes in beliefs and values about collaborative practices among teachers, which in turn led to the adoption of other collaborative practices.…”
Section: Into Practice -Degree and Quality Of Changementioning
confidence: 99%
“…Increasing international interest in teacher motivation has lead to studies specifically investigating the role of teacher motivation in retention (Muller, Alliata, & Benninghoff, 2009;Sinclair, 2008;Skaalvik & Skaalvik, 2011) and teacher motivation and resilience (Kitching, et al, 2009). Are resilient teachers more motivated?…”
Section: The Four Dimensional Framework Of Teacher Resiliencementioning
confidence: 99%
“…Among these are protective factors that include attributes such as altruism (Brunetti, 2006;Chong & Low, 2009), strong intrinsic motivation (Flores, 2006;Kitching, Morgan, & O'Leary, 2009), perseverance and persistence (Fleet, Kitson, Cassady, & Hughes, 2007;Sinclair, 2008), optimism (Chong & Low, 2009;Le Cornu, 2009), sense of humour (Bobek, 2002;Jarzabkowski, 2002), emotional intelligence (Chan, Lau, Nie, Lim, & Hogan, 2008), willingness to take risks (Sumsion, 2003) and flexibility (Le Cornu, 2009). Such attributes may assist early career teachers to 'bounce back' despite the challenges of the first years of teaching.…”
mentioning
confidence: 99%
“…In his research on teachers working in inner-city high schools in the United States, Brunetti (2006) defined teacher resilience as 'a quality that enables teachers to maintain their commitment to teaching and teaching practices despite challenging conditions and recurring setbacks ' (2006, p. 813). Over time research has also consistently found that teachers' self-efficacy beliefs as to whether they have the capacity to effectively help children learn and achieve are one of the most important factors influencing teachers' resilient qualities (Kitching et al, 2009;Morgan et al, 2010;Hong, 2012). In this sense, resilient teachers are not survivors in the profession because they 'do more than merely get through difficult emotional experiences, hanging on to inner equilibrium by a thread ' (O'Connell Higgins, 1994, p. 1; see also Gu and Li, 2013).…”
Section: What We Already Knowmentioning
confidence: 99%